Innovating in Krugman's Footsteps – Where and How Innovation Differs in Europe: Static Innovation Indicators for Identifying Regional Policy Leverages - Imke Rhoden (ZBW – Leibniz Information Centre for Economics, 2020)
This paper introduces two indicators for innovation, showing the allocation of innovation and its inherent diversity. Both indicators can give insights for regional innovation policy conception. The first indicator measures the share of patents in research and development expenditure, proposing a locational innovation output indicator. It can show that innovation in Europe differs strongly among NUTS2-level regions, which points to regionally specific, place-based policies as a result of a strong dispersion in European innovation activity. The second measure, the innovation diversity indicator, shows the diversification of innovation in a region and is built upon Krugman's locational Gini coefficients. Here, the share of patents belonging to a particular IPC class is related to the dispersion of all patents in a region. Possible implications for policy are the construction of place-based, technology-specific programs, on either national or subnational (NUTS2-) level, where each country or region has to be considered carefully. Analyses underline that innovation in Europe is a highly regionally and technically diversified concept. – – Dieses Papier stellt zwei Indikatoren für Innovation vor, die die Allokation von Innovation und ihre Vielfalt aufzeigen. Beide Indikatoren können Erkenntnisse für die Konzeption regionaler Innovationspolitik liefern. Der erste Indikator misst den Anteil von Patenten an den Forschungs- und Entwicklungsausgaben und schlägt einen Indikator für standortbezogenen Innovationsoutput vor. Er kann zeigen, dass sich die Innovation in Europa zwischen den Regionen der NUTS2-Ebene stark unterscheidet, was auf eine regionalspezifische, standortbezogene Politik infolge einer starken Streuung der europäischen Innovationsaktivitäten hinweist. Das zweite Maß, ein Indikator für Innovationsvielfalt, zeigt die Diversifizierung von Innovation in einer Region und baut auf Krugmans standortbezogenen Gini-Koeffizienten auf. Hier wird der Anteil der Patente, die zu einer bestimmten IPC-Klasse gehören, mit der Streuung aller Patente in einer Region in Beziehung gesetzt. Mögliche Implikationen für die Politik sind die Konstruktion ortsbezogener, technologiespezifischer Programme entweder auf nationaler oder subnationaler (NUTS2-) Ebene, wobei jedes Land oder jede Region individuell betrachtet werden sollte. Die Analysen unterstreichen, dass Innovation in Europa ein stark regional und technisch diversifiziertes Konzept ist.
Keywords: R12; O33; O38; 330; Innovation Indicator; Innovation Gini; Regional Dispersion; Research and Development Allocation; Patent Data